Is radiofrequency ablation of varicose veins a valuable option? A systematic review of the literature with a cost analysis - Poder, Thomas G. (Can J Surg, 2018)
BACKGROUND: Since the 1990s, new techniques for the treatment of varicose veins have emerged, including radiofrequency ablation (RFA) and laser treatment. We performed a study to compare the safety, efficacy and outcomes of RFA compared to those of open surgery and laser ablation for the treatment of varicose veins. We also carried out a cost analysis of RFA compared to open surgery to assess whether RFA could help free up operating room time by being performed in an outpatient context. METHODS: We conducted a systematic literature review (publication date May 2010–September 2013 for articles in English, January 1991–September 2013 for those in French). We used several checklists to measure the quality of the studies. We also collected data on costing. RESULTS: The literature search identified 924 publications, of which 38 were retained for analysis: 15 literature reviews, 1 good-practice guideline and 22 new primary studies. The overall level of evidence was low to moderate owing to the limited sample sizes, lack of information on patient characteristics and lack of standardization of the outcome measures. However, the results obtained are consistent from study to study. In the short and medium term, RFA is considered as effective as open surgery or laser treatment (moderate level of evidence) and presents fewer major and minor complications than open surgery (low level of evidence). Radiofrequency ablation can be performed on an outpatient basis. We calculated that RFA would be about $110–$220 more expensive per patient than open surgery. CONCLUSION: Radiofrequency ablation is a valuable alternative to open surgery and would free up operating room time in a context of low accessibility.